2004
DOI: 10.1080/10473289.2004.10471018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Post-Harvest Biomass Burning Aerosols in Gwangju, Korea

Abstract: The main objective of this study was to investigate the chemical characteristics of post-harvest biomass burning aerosols from field burning of barley straw in late spring and rice straw in late fall in rural areas of Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 13 publications
2
45
0
1
Order By: Relevance
“…Another probable cause could be due to barbecue parties popularly held during autumn events in Korea, where a significant amount of OC aerosols can also be emitted (Ryu et al, 2004).…”
Section: Particle Typesmentioning
confidence: 99%
“…Another probable cause could be due to barbecue parties popularly held during autumn events in Korea, where a significant amount of OC aerosols can also be emitted (Ryu et al, 2004).…”
Section: Particle Typesmentioning
confidence: 99%
“…3(b)) were dominant in the fine particles (0.18-1.8 μm) due to burning of vegetative material, i.e., rice straw, during the sampling period in Daliao, where there are some agricultural activities. Ryu et al (2004) investigated biomass-burning aerosols and found that Cl -, NO 3 -, SO 4 2-, NH 4 + , and K + were the major ionic species in the particles. K + is the major electrolyte in cell cytoplasm, which is released in large amounts of K-rich particulates in the submicron size fraction (Andrease et al, 1983(Andrease et al, , 1998.…”
Section: Water-soluble Ionic Speciesmentioning
confidence: 99%
“…The concentration of total suspended particles (TSP) was also higher due to the effect of fugitive dust, which is generally significant in rural areas in Korea. In the measurements of PM 10 conducted in spring and fall of both 2007 and 2008 at the same site, K + was highly correlated with secondary inorganic ions such as SO 4 2− and NO 3 − , indicating the influence of biomass burning on the photochemical production (Maxwell-Meyer et al, 2004;Ryu et al, 2004Ryu et al, , 2007Won et al, 2010).…”
Section: Measurement Sitementioning
confidence: 95%